Terson Syndroms - Nowosielska, Agnieszka; Czarnecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The syndrome of intra-vitreous bleeding in association with subarachnoid haemorrhage (SAH) was first describe by French ophthalmologist Albert Terson in 1900. In last 10 years only a few cases were recorded. Early recognition of TS is of high importance, since diminution of visual acuity even to functional blindness, can hamper the rehabilitative process. The treatment methods are various, based on clinical manifestation. The surgical procedure of choice is the pars plana vitrectomy (PPV). The importance of being aware of the syndrome is very crucial, both in order to provide the adequate nursing care and to be able to perform early vitrectomy, to restore the visual function.